ANALISIS KINERJA MESIN ROTARY DRYER BERBAHAN BAKAR GAS LPG UNTUK PENGERINGAN GABAH - Ritonga, Abdul Mukhlis; Mustaufik, Mustaufik; Hitapriya , Adeka Sangtraga; Khasanah, Jannata Utswatun (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Drying of grain is a process to reduce the water content. One of the obstacles in the drying process is the weather factor. The use of a rotary dryer with LPG gas fuel can be used as an alternative to dry grain. The purpose of this study was to determine the performance of the rotary dryer in grain drying including the optimum machine capacity, reduction in the moisture content of the material, drying energy, drying rate, and drying efficiency. The research method used is the experimental method. The condition of the grain moisture content tested was water content between 18%-22% and thermostat temperature between 50°C-60°C (treatment 1), moisture content between 23%-27%, and thermostat temperature between 60°C-70° C (treatment 2) with a total mass of 500 kg of grain. The results showed that the rotary dryer machine can be used to dry grain efficiently. The rotary dryer machine produces an average optimum capacity of 104.02 kg/hour in treatment 1 and 111.90 kg/hour in treatment 2, the decrease in water content in treatment 1 is 5.92% and in treatment 2 is 8.65%, drying energy in average 188.453 .1 kJ in treatment 1 and 162.862.7 kJ in treatment 2, Drying rate on average 2.71 % db/hour in treatment 1 and 4.47 % db/hour in treatment 2, Drying efficiency on average 32.67% in treatment 1 and 50.92 % in treatment 2.